مقولات الشعراء الأمويين النثرية في نقد الشعر - يعقوب, عبد الكريم; اسكندر, سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
اعتادت الدراسات النقدية تناول قضايا الشعر من وجهة نظر النقاد الذين قرؤوا الشعر، ودرسوه، وفندوه حتى خرجوا بمقولاتهم النقدية. فقد كان الشعر أساس هذه الدراسات، لتقصر مهمة الشاعر على إبداع الشعر ونظمه، مغفلة رأي الشاعر نفسه بما ينظم، فجاء البحث ليسلط الضوء على وجهة نظر صانع الشعر بما صنع، فجاءت مقولات الشعراء النثرية لتظهر رؤيتهم الخاصة، وتبين مفهومهم للشعر و نقده. بدأ نقد الشعراء للشعر منذ الجاهلية، ولا أدل على ذلك من الخيمة التي كانت تنصب للشاعر الكبير النابغة الذبياني، والآراء النقدية التي كان يطلقها في الحكم على ما يسمع من شعر الشعراء الذين يأتون إليه. وإن كانت معظم هذه الأحكام ذوقية غير معللة، إلا أنها كانت محكومة بتجربة الذبياني الشعرية الكبيرة ومعرفته وخبرته بأفانين الشعر وأدواته؛ لذلك كانت لهذه الآراء أهمية كبرى بين الشعراء، حتى إن بعضهم كان يتفاخر أن النابغة فضّله على غيره من الشعراء. وقد استمرت هذه الروح النقدية حتى العصر الأموي؛ إذ نجد آراءً لشعراء أمويين في شعرٍ قاله غيرهم من الشعراء. كشفت هذه الآراء النقاب عن الجانب النقدي عند الشعراء، وكيف التقى الجانب الإبداعي الذي تمثل في نظم الشعر، فكانت آراؤهم النقدية الموجه لهم في أثناء نظمهم الشعر، كما كان الشعر أساس مقولاتهم النقدية. The perspectives of the critics have usually informed literary studies, critics who formed their sayings or critiques after reading, studying and exploring the depths of poetry. Poetry itself has been the basis of these studies. However, the role of poet was merely limited to poetry-writing. The poet`s point of view regarding the material he/she has produced was completely ignored. Hence the emergence of research presenting the sayings of the poet themselves as well as the poets` prosaic sayings expressing their perception as well as conception of the art of writing poetry. Jaahili period witnessed the emergence of the poets` criticism of poetry. That was evident in Alnabegha Alzubyani` tent where he used to make judgments and critiques of the poems he heard. These judgments, however, were not based on theory; they were rather the product of the poet`s profound knowledge as well as experience of the art of writing poetry. Therefore, these judgments were considerably important for poets to the extent that the poets he applauded used to blow their own trumpets. This critical spirit survived in the Omayyad period. The Omayyad poets frequently used to give opinions and make judgments on their peers` writing. These opinions had revealed the poets` critical aspect which had met their poetic one, the latter been materialized in poetry-writing. These critical views underpinned the Omayyad poets` perspective in poetry-writing, exactly as poetry had underpinned their critical opinions.